Rising Carcinogenic Risk from Polycyclic Aromatic Hydrocarbon Exposure Through Indoor Settled Dust: First Comprehensive Residential Dust Assessment from India - Kurian Ronnie Rex; Subramani Shanmugavel; Ishan Singh; Gajanan Kanade; Khushi Wankhede; Sanjeev Kumar Singh; Asirvatham Ramesh Kumar (International Journal of Environmental Research, 2026)

Check-dams as monitoring windows for ecological collapse and microplastic trapping: diatom bioassessment and sediment-core evidence from the Cooum River basin - Sagaya John Paul Joseph; Manjupriya Ayyanar; Lakshmi Priyaa Marimuthu; Sathish Kumar Boopathi; Parvana Chengolikkandi; Subramani Nagaraj (Environmental Monitoring and Assessment, 2026)

Are unreported technical polychlorinated biphenyl formulations used in legacy building materials threatening indoor environments of a central Indian City despite the ban? - K. Ronnie Rex; S. Subramani; Ishan Singh; Gajanan Kanade; Khushi Wankhede; A. Ramesh Kumar (Journal of Hazardous Materials, 2026)

Enhanced Electrokinetic Remediation of Polychlorinated biphenyls in Transformer Oil-Contaminated Soils: Synergistic Application of Surfactants and Oxidants for PCBs Removal - Pradip Jadhao; Ankur Khare; S. Subramani; Gajanan Kanade; A. Ramesh Kumar (Water, Air, & Soil Pollution, 2026)

Transforming residues to resources: agricultural waste management for value added products, bioenergy, and sustainable economic growth - Aquiny Befairlyne T Mawthoh; Devina Seram; Haobijam James Watt; Nadir Ayrilmis; Thirukkumar Subramani; Naveen Kumar Pandurangan; Hrishikesh Patil; Jayaasree Aruljothi (Environment, Development and Sustainability, 2026)

Extended Producer Responsibility in Mitigating E-waste: A Study of Mobile Phone Users in India - Abhijat Abhyankar; J. S. Sudarsan; Anand Prakash; Anandha Kumar Subramani; Murali G; Vishal Bhalla; Keerat Kumar Gupta (Circular Economy and Sustainability, 2026)

Dictyopteris delicatula extract-based bio-coating: a sustainable strategy for extending postharvest shelf life in Climacteric fruits - Sathish Kumar Boopathi; Srioviya Jayabalan; Sagaya John Paul Joseph; Antony Prakash Rejoy Patrick; Arunkumar Kulanthaiyesu; Nagaraj Subramani (Sustainable Chemistry and Pharmacy, 2026)

A GIS-based multi-criteria decision-making approach for environmentally sustainable landfill site selection: a case study from an Indian smart city - Kirubakaran Muniraj; Colins Johnny Jesudhas; Balamurugan Panneerselvam; Anandha Kumar Subramani; Suresh Devaraj; Anand Balasubramanian; Elgiva John (Innovative Infrastructure Solutions, 2026)

Identification of QTLs Responsible for Fodder Quality Traits in Fodder Maize (Zea mays L.) - Pawan Kumar Dash; Palaniyappan Subramani; Ganesan Kalipatty Nalliappan; Manivannan Narayana; Vellaikumar Sampathrajan; Senthil Natesan (Indian Journal of Genetics and Plant Breeding, 2026)

Haploids (n) possess significantly compromised morphological, physiological and biochemical attributes over diploid (2n) plants in maize - Suman Dutta; Sudhir Kumar; Vignesh Muthusamy; Rajkumar U. Zunjare; Subhra J. Mishra; Nisrita Gain; Botta T. Ganesh; Ravindra K. Kasana; Jayanthi Madhavan; Rajkumar Subramani; Firoz Hossain (Cereal Research Communications, 2026)

Occurrence, sources, and risk assessment of organophosphate flame retardants and phthalate esters in playground soils across an urban–rural gradient in central India - K. Ronnie Rex; Ishan Singh; S. Subramani; Sanjeev Kumar Singh; Gajanan Sitaramji Kanade; A. Ramesh Kumar (Environmental Geochemistry and Health, 2026)

Polychlorinated Biphenyls in India: Fading Legacy or Persistent Threat? A Review of Environmental Contamination, Sources, Exposure Risks, and Regulatory Commitments - K. Ronnie Rex; S. Subramani; A. Ramesh Kumar (International Journal of Environmental Research, 2025)

Mining overburden sand from lignite mines as a partial replacement for fine aggregates in concrete - B. Balakrishna Prasanna; G.R. Senthil Kumar; P. Gopinathan; Amit Karmakar; Md Mustaque Ansari; T. Subramani (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

PINTO: Physics-informed transformer neural operator for learning generalized solutions of partial differential equations for any initial and boundary condition - Sumanth Kumar Boya; Deepak N. Subramani (Computer Physics Communications, 2025)

Accelerated development of MTL and DMP gene-based subtropically-adapted maternal haploid inducer lines in maize using molecular breeding - Nisrita Gain; Vignesh Muthusamy; Rashmi Chhabra; Amitkumar D. Kyada; Suman Dutta; Gulab Chand; Ravindra K. Kasana; Konsam Sarika; Elangbam L. Devi; Jayanthi Madhavan; Rajkumar Subramani; Rajkumar U. Zunjare; et al. (Planta, 2025)

Ecological dynamics and biodegradation potential of freshwater epiplastic microalgae: A sustainable solution for plastic waste management - Sagaya John Paul Joseph; Jayashree K; Sathish Kumar Boopathi; Antony Prakash Rejoy P; Poornima S; Nagaraj Subramani (Journal of Water Process Engineering, 2025)

Structural and maturity evolution of lignite using Raman spectroscopy and organic petrology of the Barmer basin, Rajasthan, India - Om Prakash Kumar; P. Gopinathan; Amiya S. Naik; Pramod K. Rajak; Govind Kumar; Neeraj K. Upadhayay; Amit Karmakar; T. Subramani (Environmental Geochemistry and Health, 2025)

Health risks due to geogenic and anthropogenic influences on groundwater quality in Southern India's hard rock terrain - B. Preethi; T. Subramani; R. Saravanan; P. Gopinathan; Zaixing Huang; Brajesh Kumar (Journal of Geochemical Exploration, 2025)

Advancements in the production methods and recycling of multilayer plastics with sustainable applications: A comprehensive review - Maha Awjan Alreshidi; Krishna Kumar Yadav; G. Shoba; Amel Gacem; S. Padmanabhan; T. Vinod Kumar; Ahmed M. Fallatah; Javed Khan Bhutto; Fahad M. Aldosari; Manawwer Alam; Muhammad A. Abo El-Khair; P. Tamizhdurai; et al. (Chemical Engineering Journal, 2025)

Utilization of charnockite rock as manufactured-aggregate for construction industry: a case study from Thiruvakkarai quarry and M-sand plant in Tamil Nadu, India - B. Balakrishna Prasanna; G. R. Senthil Kumar; T. Subramani; Ramamohana Reddy Bellum (Environmental Geochemistry and Health, 2025)

Nitrate pollution index and age wise health risk appraisal for the Pambar River basin in south India - C. N. Sridhar; T. Subramani; G. R. Senthil Kumar; K. Soundaranayaki (Environmental Geochemistry and Health, 2025)

Deep Learning in Analyzing Carbon Flux Patterns for Environmental Health: Remote Sensing Insights for Climate Mitigation Strategies - Hariharan Subramani; M. Neela Harish; Selva kumar S; P. Radhakrishnan; L. N. K. Sai Madupu; Kasturi Sai Sandeep; Divya Nimma (Remote Sensing in Earth Systems Sciences, 2025)

Molecular Diversity Studies and Core Development in Sesame Germplasm (Sesamum indicum L.) Using SSR Markers - Rasna Maurya; Shivani Singh; Yangala Sudheer Babu; Fatima Nazish Khan; Bhagwat Nawade; Harinder Vishwakarma; Ajay Kumar; Rashmi Yadav; Radhamani Jalli; Mahalingam Angamuthu; Mothilal Alagirisamy; Rajkumar Subramani; et al. (Plant Molecular Biology Reporter, 2025)

Piperazine derivatives and bioactive compounds from red seaweed Haloplegma duperreyi: A novel source for inhibition of HIV-I - Sathish Kumar Boopathi; Nagaraj Subramani; Luke Elizabeth Hanna; Lucia Precilla Karunakaran; Sagaya John Paul Joseph; Kotteswari Murugesan (Algal Research, 2025)

Renewable energy from waste plastic: Hydroprocessing of mixed waste plastic to diesel fuel utilizing Fe/Mo-Al2O3 catalyst - A. Sujithraj; P. Tamizhdurai; V.L. Mangesh; C. Kavitha; A. Subramani; P. Saravanan; P. Nisha; P. Sasikumar; Nadavala Siva Kumar; Salwa B. Alreshaidan; Ghzzai Almutairi; Ahmed S. Al-Fatesh (Process Safety and Environmental Protection, 2025)

Catalytic conversion of plastic waste into diesel fuel through pyrolysis and hydroprocessing - R. Vedavalli; P. Tamizhdurai; C. Kavitha; V.L. Mangesh; G.S.V. Seshu Kumar; P. Saravanan; A. Subramani; P. Sasikumar; Nadavala Siva Kumar; Salwa B. Alreshaidan; Abdulaziz I. Alromaeh; Ahmed S. Al-Fatesh (Process Safety and Environmental Protection, 2025)

Transformation in energy content of non-coking coals during differential settling beneficiation process: Implications for energy impact - Amit Karmakar; P. Gopinathan; Om Prakash Kumar; Manoj K. Sethi; T. Subramani; M. Santosh; Pradip K. Banerjee (Fuel, 2024)

Mineralogical and geochemical characterization of coal debris from major coal fields in India: Implications on respirable dust hazards - P. Gopinathan; M.S. Santosh; Om Prakash Kumar; T. Subramani; Vasileios Antoniadis; Sabry M. Shaheen; M. Santosh (Process Safety and Environmental Protection, 2024)

Petrographic and geochemical analysis of Barmer Basin Paleogene lignite deposits: Insights into depositional environment and paleo-climate - Om Prakash Kumar; Amiya S. Naik; P. Gopinathan; T. Subramani; Vishvajeet Singh; Prakash K. Singh; Uma K. Shukla; Arun Prabhu (Journal of Geochemical Exploration, 2024)

Investigation of indoor air pollutants in different environmental settings and their health impact: a case study of Dehradun, India - Abhishek Nandan; Prasenjit Mondal; Sandeep Kumar; Nihal Anwar Siddiqui; Shambhavi Sinha; Sudalai Subramani; Akshi Kunwar Singh; Sivashankar Raja; Chaudhery Mustansar Hussain (Air Quality, Atmosphere & Health, 2023)

Ziziphus mauritiana-derived nitrogen-doped biogenic carbon dots: Eco-friendly catalysts for dye degradation and antibacterial applications - Subramani Rajapandi; Senthilkumar Nangan; Thirumalaivasan Natesan; Anuj Kumar; Govindaraj Dharman; M. Pandeeswaran; Deepak Verma; Mohd Ubaidullah; Bidhan Pandit; Navdeep Dhaliwal; Satbir S. Sehgal; Rajavel Rangappan; et al. (Chemosphere, 2023)

Characterization of lignite deposits of Barmer Basin, Rajasthan: insights from mineralogical and elemental analysis - Om Prakash Kumar; P. Gopinathan; Amiya S. Naik; T. Subramani; Prakash K. Singh; Anupam Sharma; Sudip Maity; Sujan Saha (Environmental Geochemistry and Health, 2023)

Trihydroxy piperlongumine protects aluminium induced neurotoxicity in zebrafish: Behavioral and biochemical approach - B. Haridevamuthu; David Raj; D. Kesavan; Subramani Muthuraman; Rajendran Saravana Kumar; Shahid Mahboob; Khalid Abdullah Al-Ghanim; Bader O. Almutairi; Selvaraj Arokiyaraj; Pushparathinam Gopinath; Jesu Arockiaraj (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

The loss of cardiac SIRT3 decreases metabolic flexibility and proteostasis in an age-dependent manner - Ping Li; Maria F. Newhardt; Satoshi Matsuzaki; Craig Eyster; Atul Pranay; Frederick F. Peelor; Albert Batushansky; Caroline Kinter; Kumar Subramani; Sandeep Subrahmanian; Jasimuddin Ahamed; Pengchun Yu; et al. (GeroScience, 2023)
SIRT3 is a longevity factor that acts as the primary deacetylase in mitochondria. Although ubiquitously expressed, previous global SIRT3 knockout studies have shown primarily a cardiac-specific phenotype. Here, we sought to determine how specifically knocking out SIRT3 in cardiomyocytes (SIRTcKO mice) temporally affects cardiac function and metabolism. Mice displayed an age-dependent increase in cardiac pathology, with 10-month-old mice exhibiting significant loss of systolic function, hypertrophy, and fibrosis. While mitochondrial function was maintained at 10 months, proteomics and metabolic phenotyping indicated SIRT3 hearts had increased reliance on glucose as an energy substrate. Additionally, there was a significant increase in branched-chain amino acids in SIRT3cKO hearts without concurrent increases in mTOR activity. Heavy water labeling experiments demonstrated that, by 3 months of age, there was an increase in protein synthesis that promoted hypertrophic growth with a potential loss of proteostasis in SIRT3cKO hearts. Cumulatively, these data show that the cardiomyocyte-specific loss of SIRT3 results in severe pathology with an accelerated aging phenotype.

Experimental study on penetration characteristics of an open-ended pile under static and dynamic driving methods - Jingxue Lu; Hongfeng Guang; Lin Cui; Junwei Liu; Cheng Wang; Subramani Anandha Kumar (Soil Dynamics and Earthquake Engineering, 2023)

Thermo-economic comparison of single basin and stacked solar still configurations - Deepak Kumar Murugan; Sekar Subramani; Arunkumar Thirugnanasambantham; Karthick Munuswamy (Environmental Science and Pollution Research, 2022)

How do the sympatric forest mongooses coexist in the Western Ghats landscape? Insights from spatio-temporal approach - Thekke Thumbath Shameer; Sulekha Jameela Backer; Subramani Nandhini; Sreehari Raman; Azim Nisar Mujawar; Jayakumar Yogesh; Krishan Kumar Kaushal; Srinivas Ramachandra Reddy; Anwar Nazia; Raveendranathanpillai Sanil (Community Ecology, 2022)

Engineering Aspects of Incidence, Prevalence, and Management of Osteoarthritis: A Review - Dhirendra Kumar Verma; Poonam Kumari; Subramani Kanagaraj (Annals of Biomedical Engineering, 2022)

Epiphytic phytoplankton in response to divergent air pollutants from urban and commercial zones of Chennai District, Tamil Nadu, India: A case study towards phytoplankton based Air Quality Index - Sagaya John Paul Joseph; Sreekala Kannikulathel Gopidas; Gomathi Gnanam; Sathish Kumar Boopathi; Nagaraj Subramani (Environmental Science and Pollution Research, 2022)

Understanding the microstructure, mineralogical and adsorption characteristics of guar gum blended soil as a liner material - Anandha Kumar Subramani; Sujatha Evangelin Ramani; Rangabhashiyam Selvasembian (Environmental Monitoring and Assessment, 2021)

Guar gum-stabilized soil: a clean, sustainable and economic alternative liner material for landfills - Subramani Anandha Kumar; Evangelin Ramani Sujatha; Arulazhagan Pugazhendi; Mamdoh T. Jamal (Clean Technologies and Environmental Policy, 2021)

Impact of hydration and gelling properties of guar gum on the mechanism of soil modification - Evangelin Ramani Sujatha; Saisree Sivaraman; Anandha Kumar Subramani (Arabian Journal of Geosciences, 2020)

Evidence to Suggest Bacterial Lipoprotein Diacylglyceryl Transferase (Lgt) is a Weakly Associated Inner Membrane Protein - Nikhil Sangith; Subramani Kumar; Krishnan Sankaran (The Journal of Membrane Biology, 2019)

Z-DNA in the genome: from structure to disease - Subramaniyam Ravichandran; Vinod Kumar Subramani; Kyeong Kyu Kim (Biophysical Reviews, 2019)

Diesel reformulation using bio-derived propanol to control toxic emissions from a light-duty agricultural diesel engine - Muthukkumar Thillainayagam; Krishnamoorthy Venkatesan; Rana Dipak; Saravanan Subramani; Balaji Sethuramasamyraja; Rajesh Kumar Babu (Environmental Science and Pollution Research, 2017)

Purification of a recombinant histidine-tagged lactate dehydrogenase from the malaria parasite, Plasmodium vivax, and characterization of its properties - Balamurugan Sundaram; Nandan Mysore Varadarajan; Pradeep Annamalai Subramani; Susanta Kumar Ghosh; Viswanathan Arun Nagaraj (Biotechnology Letters, 2014)

Expressed sequence tags and molecular cloning and characterization of gene encoding pinoresinol/lariciresinol reductase from Podophyllum hexandrum - Dhammaprakash Pandhari Wankhede; Dipul Kumar Biswas; Subramani Rajkumar; Alok Krishna Sinha (Protoplasma, 2013)

Three bioactive sesquiterpene quinones from the Fijian marine sponge of the genus Hippospongia - Rohitesh Kumar; Ramesh Subramani; William Aalbersberg (Natural Product Research, 2013)

Genetic Structure of Indian Valerian (Valeriana jatamansi) Populations in Western Himalaya Revealed by AFLP - Subramani Rajkumar; Sunil Kumar Singh; Akshay Nag; Paramvir S. Ahuja (Biochemical Genetics, 2011)